(untitled) (Scientific journal of the Fergana State University, 2024)
The ability to use experiments to search for information in professional training gives special importance to the formation of experimental skills among students in vocational schools. In this sense, experimental skills can be considered as one of the main components of readiness to search for information, and formation of experimental skills is one of the stages of formation of information competence. We try to connect the definitions of experimental skills with readiness to search for information.